Influence of psychosocial factors on health behaviours among undergraduates in Malaysia - Omar Dev, Roxana Dev; Tengku Kamalden, Tengku Fadilah; Soh, Kim Geok; Abdullah, Maria Chong; Mohd Ayub, Ahmad Fauzi; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2019)
Changes in technology-oriented lifestyles and the advancement of information technology have affected university students' values, culture, thinking, lifestyle and character. Unhealthy health behaviors such as smoking and free sex have increased among university students in Malaysia (Roxana et al., 2018). If no intervention is implemented in the education system, this problematic character will become a reference that disrupts the society. Therefore, active steps should be taken to address this problem. The main aim of this study is to develop a model of health behavior by identifying the relationship of a psycho-social variant of spiritual intelligence to various mediators, which are emotional intelligence and self-efficacy towards health behavior among undergraduate students in Malaysia. The model is based on the Theory of Triadic Influence (Fly & Petraitis (1994)). The study uses four instruments namely the Health Behavior Questionnaire (adapted from Bobroff, 2015), the General Self-Efficacy Scale (Schwarzer & Jerusalem, 1993), Spiritual Inteligence Self-Report Inventory (King, 2008), and Assesssment of Emotional Scale (Schutte, Malouff & Bhullar, 2009). A randomized proportionate stratified sampling technique was used with a sample of 400 students living in the college at Universiti Putra Malaysia. The structural model of the study with 6 paths was tested and only five paths showed significant effects. This study has shed new light on measuring self-efficacy through students' perceptions. Few researchers have identified self-efficacy as an important factor in making predictions about health behaviors (Mathumardhi & Suparna, 2016; Jamshidi et al., 2018) however, high self-efficacy will be meaningless if there is no authentic way in addressing intrinsic aspects of life in terms of spirituality (Mathumardhi & Suparna, 2016; Gwahula, 2018). Spiritual intelligence and high self-efficacy can produce quality students and care about health behaviors.